Typhoons and their upper ocean response over South China Sea using COAWST model - Thankaswamy, Anandh; Xian, Tao; Wang, Lian-Ping (Frontiers in Earth Science, 2023)
The formation and intensification of typhoons is a complex process where energy and mass exchanges happen between the ocean and the atmosphere. In most typhoon numerical studies, a static ocean and a dynamic atmosphere are used to reduce the complexity of modeling. Using the COAWST model, we studied the air-sea interactions of typhoons Mujigae (2015), Merbok (2017), and Hato (2017) over the South China Sea. With different translation speeds, track shapes, and intensities between these cyclones, they act as an excellent case study to analyze the air-sea coupling in the models. The inclusion of coupling between the ocean and atmosphere is found to improve the typhoon track simulation significantly. The bias in the cyclone tracks is reduced by 10%--40% in the coupled model. The upper ocean response to the typhoon was also analyzed using the coupled model output. The coupled simulations show that the major energy extraction occurs to the right of the track, which is consistent with satellite observation and latent heat release analysis. The coupling process shows the air-sea interactions and exchanges in the upper ocean along with the energy released during the passage of typhoons. The heat budget analysis shows that the cooling of the upper ocean is mainly attributed to the advection associated with the typhoon forcing. This study shows that it is necessary to include ocean feedback while analyzing a typhoon, and the application of coupled models can improve our understanding as well as the forecasting capability of typhoons.